Tuberculous meningitis presenting as Acute Ischemic Stroke (Indian Journal of Case Reports, 2019)
Infection can cause cerebral vasculitis not only by direct invasion of the vessel wall, but by immune complex deposition, or through secondary cryoglobulinemia. Here, we report the case of tuberculous meningitis (TBM) in a middle-aged woman who presented with diabetic ketoacidosis, hyponatremia and accelerated hypertension and after 24 hours had right-sided hemiplegia. Her imaging MRI brain without contrast was suggestive of acute stroke. Hence, she was thrombolysed but she did not show any improvement. Repeat MRI brain with contrast showed tuberculomas and after starting Anti-Tubercular Treatment (ATT), she became alright within 3 days. There was no hemiplegia after 3 days of ATT. So TBM can also present as vasculitis with stroke and it should be kept in mind because recognition of TBM will change the line of treatment and patient can recover within a few days.